Environmental justice in Africa: Cultural and economic impacts on the legal systems (Pretoria University Law Press (PULP), 2025)
This book’s overarching theme is to discern the role of law in shaping environmental justice in Africa. Simultaneously, it delves into the intricate interplay of economic and cultural factors that can either facilitate or impede the pursuit of justice. Acknowledging that environmental justice transcends legal frameworks alone, the book emphasises its recognition as a social pillar integral to sustainable development. In this holistic perspective, environmental justice is positioned on equal footing with environmental protection and economic sustainability, highlighting its multifaceted nature in Africa.